Epistemologies of the South and Decolonisation of Human Rights - Vignola, Marta (PARTECIPAZIONE E CONFLITTO, 2023)
Being characterised by a variety of normative systems and systems of knowledge, contemporary societies are said to be pluralistic. Yet, some expressions of epistemic and legal pluralism are still ignored and rejected, due to the cognitive hegemony and legal centralism of Western modernity. The issue has been explored from different perspectives in the field of human and social sciences, having been investigated within the framework of Latin American neo-Marxist dependency theory, English post-colonial studies, world-systems theory, the theories of the Modernity/Coloniality group, and the Epistemologies of the South. Such approaches seem to be particularly effective when carrying out a comprehensive analysis of human rights, as global social justice cannot be achieved without global cognitive justice (de Sousa Santos 2007). Other languages can be used to talk about human dignity, with epistemic and legal pluralism making the various grammar rules of fundamental rights intelligible. Such an approach has been adopted by decolonial theory, which is experimenting with a new legal common sense. In this paper, reference will be made to the Epistemologies of the South, theorised by Portuguese sociologist of law Boaventura de Sousa Santos.